Testing the Sternal Clavicle Ageing Method on a Post‐Medieval Dutch Skeletal Collection. (17th April 2018) - Blom, A. A.; Inskip, S. A.; Baetsen, W. A.; Hoogland, M. L. P.
Abstract : When a new method is produced, it should be assessed for accuracy and reliability before widespread use. A new method by Falys and Prangle for estimating age from degeneration of the sternal end of the clavicle is tested in this paper on an 18th–19th‐century known‐age Dutch population (80 clavicles). Intra‐ and inter‐observer tests (Cohen's kappa) revealed slight to moderate agreement ( k = 0.100–0.425 and 0.106–0.534 respectively). However, owing to large age ranges, 87% accuracy was achieved. Methodological improvements are suggested that could help the method further to improve age estimates for the elderly in past populations.